Antitumor activity of colloidal silver on MCF-7 human breast cancer cells - Franco-Molina, Moisés A (BioMed Central, 2010)
BACKGROUND: Colloidal silver has been used as an antimicrobial and disinfectant agent. However, there is scarce information on its antitumor potential. The aim of this study was to determine if colloidal silver had cytotoxic effects on MCF-7 breast cancer cells and its mechanism of cell death. METHODS: MCF-7 breast cancer cells were treated with colloidal silver (ranged from 1.75 to 17.5 ng/mL) for 5 h at 37°C and 5% CO(2 )atmosphere. Cell Viability was evaluated by trypan blue exclusion method and the mechanism of cell death through detection of mono-oligonucleosomes using an ELISA kit and TUNEL assay. The production of NO, LDH, and Gpx, SOD, CAT, and Total antioxidant activities were evaluated by colorimetric assays. RESULTS: Colloidal silver had dose-dependent cytotoxic effect in MCF-7 breast cancer cells through induction of apoptosis, shown an LD(50 )(3.5 ng/mL) and LD(100 )(14 ng/mL) (*P < 0.05), significantly decreased LDH (*P < 0.05) and significantly increased SOD (*P < 0.05) activities. However, the NO production, and Gpx, CAT, and Total antioxidant activities were not affected in MCF-7 breast cancer cells. PBMC were not altered by colloidal silver. CONCLUSIONS: The present results showed that colloidal silver might be a potential alternative agent for human breast cancer therapy.